Determinação da influência do refino de grão por ECAP nocomportamento em compressão do magnésio comercialmente puro - Flavia Spitale Jacques Poggiali (2015)
ECAP (Equal Channel Angular Pressing) is a severe plastic deformation technique in which s billet is pressed through a die with two intercepting channels with equal cross section. ECAP processing, through dies with 90º and 135º, was used to refine the grain structure of commercially pure magnesium. The results show partial refinement of the structure after one pass but complete structure refinement is observed after 4 passes of ECAP processing leading to a final grain size of ~2.7m. Some samples were subjected to annealing at different temperatures. Compression testing was used to evaluate the mechanical behavior of the processed material. The results show the material exhibits anisotropic behavior after ECAP. It is also shown that grain refinement promotes a change in deformation behavior at low strain-rates. Finally, the results suggest magnesium may change the deformation mechanism and exhibit ductile behavior when the grain structure is fine and deformation takes place at low strain rates or moderate temperatures.